2021
DOI: 10.1029/2020wr028533
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Washoff of Spores From Concrete and Asphalt Surfaces

Abstract: The fate and transport of pollutants in urban settings is dictated by numerous complex environmental processes. Urban microclimates, short pollutant travel times, and intricate flow routing around buildings make the identification of migration pathways and the quantification of contamination on surfaces and in storm water runoff challenging. Following a wide-area pathogenic biological release, such as of Bacillus anthracis (the causative agent of anthrax), consequence management activities including sampling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Further, the mechanics of actual rainfall were not included in study design, and incorporating the kinetic energy, droplet size, and runoff velocity of water in future efforts could be more representative of real-world conditions ( Mikelonis et al., 2021 ). The selection of concrete depth for conducting modeling is another area of improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the mechanics of actual rainfall were not included in study design, and incorporating the kinetic energy, droplet size, and runoff velocity of water in future efforts could be more representative of real-world conditions ( Mikelonis et al., 2021 ). The selection of concrete depth for conducting modeling is another area of improvement.…”
Section: Resultsmentioning
confidence: 99%
“…high initial concentration release into the stormwater runoff followed by exponential decay) (Charbeneau & Barrett, 1998; Water World and Environmental Resources Conference, 2004). Spraying with a high‐powered pressure washer may remove higher levels of spores than natural removal through single rain events, which are predicted to remove less than 5% of spore loading (Mikelonis et al, 2021). Percent removal by garden hose washing approximates what has been observed from simulated rainfall removal (1‐h duration, 15–115 mm/h intensity events).…”
Section: Discussionmentioning
confidence: 99%
“…RDS is an important source of metal pollution in the surrounding rivers and coastal areas (Skorbilowicz et al, 2022;Jeong et al, 2020b;2020c). The roughness of the paved road surface, the relative abundance of RDS by particle size, and the intensity of precipitation influence the transport processes and pathways of RDS particles to the surrounding environment along with stormwater runoff (Mikelonis et al, 2021;Zhao et al, 2018;2022). Many studies have found that the heavy metal concentration in RDS increases with decreasing particle size (Jeong and Ra, 2022a;Logiewa et al, 2020).…”
mentioning
confidence: 99%